Re-description of the last instar of Remartinia luteipennis luteipennis (Burmeister, 1839) (Odonata: Aeshnidae) - del Palacio, Alejandro (2019)
The final instar of Remartinia luteipennis luteipennis (Burmeister, 1839) is described and illustrated based on reared specimens from Salta Province, Argentina. It is compared with R. secreta and R. l. florida, and with Calvert’s original description of R. l. luteipennis. Remartinia l. luteipennis can be differentiated by the length of the lateral valvae of the female gonapophyses (equal to the central ones in R. l. luteipennis, slightly shorter in R. secreta, and longer in R. l. florida), and length of S6 lateral spines (1.24 mm in R. l. luteipennis 0.4–0.5 mm in R. secreta, and 0.2 mm in R. l. florida)